The Halos and Environments of Nearby Galaxies (HERON) Survey. Issue Volume 11:Issue S321(2015) (21st March 2017) - Rich, R. Michael; Brosch, Noah; Bullock, James; Burkert, Andreas; Collins, Michelle; de Groot, Laura; Kennefick, Julia; Koch, Andreas; Longstaff, Francis; Sales, Laura
Abstract: We have used dedicated 0.7m telescopes in California and Israel to image the halos of ~ 200 galaxies in the Local Volume to 29 mag/sq arcsec, the sample mainly drawn from the 2MASS Large Galaxy Atlas (LGA). We supplement the LGA sample with dwarf galaxies and more distant giant ellipticals. Low surface brightness halos exceeding 50 kpc in diameter are found only in galaxies more luminous than L *, and classic interaction signatures are relatively infrequent. Halo diameter is correlated with total galaxy luminosity. Extended low surface brightness halos are present even in galaxies as faint as MV = - 18. Edge-on galaxies with boxy bulges tend to lack extended spheroidal halos, while those with large classical bulges exhibit extended round halos, supporting the notions that boxy or barlike bulges originate from disks. Most face-on spiral galaxies present features that appear to be irregular extensions of spiral arms, although rare cases show smooth boundaries with no sign of star formation. Although we serendipitously discovered a dwarf galaxy undergoing tidal disruption in the halo of NGC 4449, we found no comparable examples in our general survey. A search for similar examples in the Local Volume identified hcc087, a tidally disrupting dwarf galaxy in the Hercules Cluster, but we do not confirm an anomalously large half-light radius reported for the dwarf VCC 1661.